PENGARUH DISIPLIN KERJA DAN PEMBERIAN KOMPENSASI TERHADAP KINERJA KARYAWAN BAGIAN PENJUALAN DI PT. SURYA TIMUR SAKTI JATIM - Novianto Eko Nugroho (Universitas Madura, 2020)
Employee performance is a form of performance in terms of quality and quantity achieved by an employee in carrying out their duties in accordance with the responsibilities given to him. Improving employee performance is desirable both from the employer and workers for self-development and promotion of the position. The purpose of this study is to determine the effect of work discipline and compensation for employee performance in sales. This research method uses quantitative methods with the type of explanatory research. The subjects of this study were all sales employees of PT. Surya Timur Sakti East Java in Surabaya, amounting to 107 active employees. To test the effect between variables used multiple linear regression analysis method. The results showed that the presence of a positive and significant effect simultaneously between variables of work discipline and compensation for employee performance, while partially the variables of work discipline and compensation had a positive and significant effect on employee performance.